2000
DOI: 10.1084/jem.191.7.1209
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Effects of Transmembrane and Soluble FAS Ligand Expression on Inflammation and Tumor Cell Survival

Abstract: Fas ligand (FasL) has been shown to mediate both apoptotic and inflammatory reactions. To rigorously assess the physiological role of different forms of the FasL molecule with regard to these two distinct processes, we isolated stably transfected lymphoma cell lines that expressed either murine wild-type FasL, membrane-only FasL, or functionally distinct forms of soluble FasL. First, the ability of these lines to induce an inflammatory response was assessed in vivo by injecting the transfectants intraperitonea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
225
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(241 citation statements)
references
References 55 publications
15
225
1
Order By: Relevance
“…Consistent with previous reports, [13][14][15][16] we found a massive neutrophil infiltration in the FasL high tumor (Figure 4). FasL med tumor induced a moderate inflammation, in agreement with their reduced growth rate compared with the parental tumors.…”
Section: Local Inflammation Induced By Fasl On Tumorssupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with previous reports, [13][14][15][16] we found a massive neutrophil infiltration in the FasL high tumor (Figure 4). FasL med tumor induced a moderate inflammation, in agreement with their reduced growth rate compared with the parental tumors.…”
Section: Local Inflammation Induced By Fasl On Tumorssupporting
confidence: 93%
“…23 A recent study provided evidence that FasL-triggered inflammation correlated with its cytotoxic activity and was in fact a secondary effect of the locally induced apoptosis. 16 Accordingly, the induction of inflammation may depend not only on the level of FasL on tumors but also on the FasL susceptibility of the surrounding tissues. It is possible that certain human tumors may express high levels of FasL to counterattack the immune effector cells without inducing an inflammatory response if their adjacent tissues are resistant to Fasmediated apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that membranebound FasL can more effectively induce apoptosis in Fasexpressing cells than soluble FasL. 24 Recently, it has been reported that the TRAIL-mediated killing pathway on immune cells also plays an important role in elimination of tumor cells. 25 We tested whether soluble TRAIL would induce apoptotic cell death of parental D122 and cytokine transfectants.…”
Section: Fas-and Trail-mediated Apoptotic Pathways In Paretnal D122 Amentioning
confidence: 84%
“…For instance, MMP-7 is capable of cleaving Fas ligand (FasL), resulting in soluble FasL (sFasL). This sFasL can then bind to Fas receptor on tumor cells and the complex is rapidly internalized, resulting in down regulation of Fas-receptor [148].…”
Section: The Role Of Mmps In Tumor Angiogenesis and Tumor Growthmentioning
confidence: 99%